PENGARUH PIJAT OKSITOSIN TERHADAP KELANCARAN ASI PADA IBU NIFAS DI PUSKESMAS SITINJO KABUPATEN DAIRI TAHUN 2019 - Herna Rinayanti Manurung (STIKes Mitra Husada Medan, 2020)
Infants who have received exclusive breastfeeding in Indonesia, namely infants up to the age of 6 months, amounted to 29.5%, this is not in accordance with the target of the Ministry of Health Strategic Plan for 2015-2019, namely the percentage of 50%. Nationally, the coverage of infants gets exclusive breastfeeding at 61.33%. One of the law exclusife breastfeeding causes is less amount of breast milk production in the first day after giving a birth which is caused by less oxcytocin and prolactin hormones stimulation in which they have a role to smoothen breast milk production that causes breast milk couldn’t immediately out after giving a birth. The nonfarmakologis effort, oxytocin massage is reguired to make the breast milk out. To know The Effect of Oxytocin Massage on Pospartum Mother Breast Milk Production Sitinjo Community Health Clinic In 2019. This resarch used quasi experiment method with pre post test control group design. The sampling technique with Purposive sampling with the number of respondent as many 34 samples, namely 17 samples for the intervention group and 17 people with the control group. Data analysis applied the Independent sample Test-T. The result of th bivariate analysis showed that the p-value p=0,000 (p<0,05), which thus, it can conclude that Ha was accepted.: of the study shows that there is a significant influence between massage of octocin and the smoothness of breast milk in Puskesmas Sitinjo, Dairi Regency, North Sumatra Province. Keywords : oxytocin, massage, breastfeeding, smooth ASI